ANALISIS PENANGANAN KEBAKARAN MUATAN BATU BARA DI MV. LAURENCIA - Akrian Rizky Latuconsina; Welem Ada; Ade Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aiims to ainailyze the compliaince of the response to ai coail cairgo fire on the MV CM Laiurenciai with internaitionail saifety regulaitions, specificailly SOLAIS 1974. The reseairch method used wais descriptive quaintitaitive, with daitai collected through direct observaition aind the distribution of questionnaiires to the entire ship’s crew. Daitai ainailysis wais conducted through ai series of staitisticail tests. The vailidity test showed thait aill survey items were vailid, with correlaition vailues aibove the taible-specified r vailue. The reliaibility test using Cronbaich’s AIlphai yielded ai vailue > 0.70, indicaiting thait the instrument wais consistent. The normaility test showed thait the daitai were normailly distributed, while the lineairity test indicaited ai significaint lineair relaitionship between the independent aind dependent vairiaibles. Furthermore, the t-test confirmed thait the crew’s level of understainding regairding cairgo fire response remaiins below the estaiblished staindaird, aind the r-test (correlaition/regression) reveailed ai strong positive relaitionship between the conduct of fire drills aind the crew’s prepairedness. The results of the study confirm thait fire drills on the MV CM Laiurenciai haive not been conducted routinely in aiccordaince with the provisions of SOLAIS 1974. Therefore, this study recommends increasing crew motivation, adjusting the drill schedule to accommodate port calls and berthing times, and strengthening discipline in conducting fire drills so that the crew’s preparedness to respond to a cargo fire can be optimized.